The general quasi-order algorithm in number theory - Peter Hilton; Jean Pedersen (International Journal of Mathematics and Mathematical Sciences)
This paper deals with a generalization of the Binary Quasi-Order Theorem. This generalization involves a more complicated algorithm than (0.2)t. Some remarks are made on relative merits of two dual algorithms called the ψ-algorithm and the ϕ-algorithm. Some illustrative examples are given.